Soft law and the development of norms and trust in countering the terrorist threat: Engaging the faith communities in post-9/11 Singapore - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2017)
On July 6, 2010, Singapore's Internal Security Department (ISD) announced that a “self-radicalized,” full-time national serviceman had been detained under the Internal Security Act (ISA) since April 4, 2010. Muhammad Fadil bin Abdul Hamid (Fadil), age 20, would be detained under the ISA for two years in the first instance. According to the media statement, Fadil had become convinced that “it was his religious duty to undertake armed jihad alongside fellow militants and strive for martyrdom.” According to local media reports, Fadil was the sixth known case of self-radicalization. Fadil was subsequently released on a Restriction Order on April 4, 2012.